Pengaruh Metode Peer Education Terhadap Perubahan Pengetahuan dalam Pencegahan Skabies di Pesantren Aceh Besar - Dewi Sartika (Pusat Riset dan Inovasi Nasional, 2025)
Scabies is a contagious skin disease that remains a significant public health problem, particularly in developing countries such as Indonesia. This disease is commonly found in densely populated environments, including Islamic boarding schools and orphanages, where close physical contact and limited sanitation practices facilitate rapid transmission. Effective prevention of scabies requires adequate knowledge, awareness, and healthy behavioral practices among individuals at risk. Therefore, innovative educational strategies that are participatory and contextual are urgently needed. This study aims to analyze the effect of health education using the peer education method on students’ knowledge in preventing scabies. The research applied a quasi-experimental design with a one-group pre-test and post-test approach. The population of the study consisted of all students in the selected institution, and the total sampling technique was used so that every student became part of the research sample. Data were collected through structured questionnaires assessing knowledge about scabies transmission, symptoms, prevention, and treatment. Statistical analysis was performed using the paired sample t-test to measure differences between pre-test and post-test scores. The results of the study showed a significant increase in students’ knowledge after receiving health education through peer education. The paired sample t-test revealed a p-value of 0.000, which is less than 0.05, indicating a statistically significant difference between pre-test and post-test results. These findings demonstrate that peer education is an effective method for improving knowledge in scabies prevention. By involving peers as educators, the program fosters more interactive communication, increases student engagement, and enhances the likelihood of knowledge retention and behavioral change. In conclusion, health education using the peer education method has a positive impact on students’ knowledge regarding scabies prevention.